2000
DOI: 10.1034/j.1600-0536.2000.043003161.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of multiparametric skin bioengineering in a prospectively‐followed cohort of junior hairdressers

Abstract: There is conflicting evidence concerning predictors of individual susceptibility to develop irritant contact dermatitis in wet work. A cohort of initially 92 hairdresser apprentices was prospectively followed for 3 years. The association between anamnestic and clinical findings, and multiparametric skin bioengineering data (transepidermal water loss [TEWL], microcirculation, capacitance, pH, sebum, temperature) was investigated. The observation intervals were 3 months in the 1st year of training and 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 15 publications
5
74
1
5
Order By: Relevance
“…Common opinion is that wet work-correlated hand dermatitis and hand eczema is more frequent in trainee hairdressers than in master hairdressers because trainees have to wash (customers) hair more often: in one prospective German study (John et al 2000), contact dermatitis in trainee hairdressers was observed during a 2-year period. The observation intervals were 3 months in the 1st year of training and 12 months thereafter.…”
Section: Discussionmentioning
confidence: 98%
“…Common opinion is that wet work-correlated hand dermatitis and hand eczema is more frequent in trainee hairdressers than in master hairdressers because trainees have to wash (customers) hair more often: in one prospective German study (John et al 2000), contact dermatitis in trainee hairdressers was observed during a 2-year period. The observation intervals were 3 months in the 1st year of training and 12 months thereafter.…”
Section: Discussionmentioning
confidence: 98%
“…To assess skin barrier function, usually the measuring of transepidermal water loss (TEWL) has been used. Several prospective field studies have investigated whether increased TEWL and hence reduced skin barrier modify the risk for OCD (mainly ICD) 14,[43][44][45] . The majority of these studies didn't find any association between pre-exposure TEWL value and the incidence of CD, not even when different barrier function parameters were combined.…”
Section: Skin Barrier Conditionmentioning
confidence: 99%
“…Several tests based on the response to experimentally induced irritation have been proposed for the identification of susceptible individuals in the work place 43,45,63,89,90) . Traditionally, the response to skin irritants has been assessed by measuring TEWL and erythema, and only recently also the levels of pro-and antiinflammatory cytokines in the skin 47,91) .…”
Section: Response To Skin Irritantsmentioning
confidence: 99%
“…Jego oceny dokonywano m.in. u uczniów zawodu fryzjera (15,16), piekarza i cukiernika (17), pracowników przemysłu metalowego (18)(19)(20), przetwórstwa rybnego (21), małych zakładów gastronomicznych (22), u zatrudnionych w warunkach niskiej wilgotności powietrza (23), pracowników rafinerii metali nieszlachetnych (24) i działu wysyłkowego drukarni gazet (12). Stosunkowo często badane grupy rekrutowały się ze służby zdrowia, a w ich skład wchodziły uczennice lub studentki szkół pielęgniarskich (15,25), pielęgniarki zatrudnione na sali operacyjnej (26), pielęgniarki geriatyczne (27) czy pracownicy ośrodka neonatologicznego (28).…”
unclassified
“…Takie badania dotyczyły np. zatrudnionych w warunkach niskiej wilgotności powietrza (20), pracowników przetwórstwa rybnego (21), działu wysyłkowego drukarni gazet (12), rafinerii metali nieszlachetnych (24), małych zakładów gastronomicznych (22), personelu sprzątającego (31) i uczniów zawodu fryzjera (16). W niektórych eksperymentach odnotowano znaczący wpływ warunków pracy na badany parametr.…”
unclassified